A Comparative Clinical Study Of Shirishadi Sharir Daurgandhyahara Powder And Its Spray In The Management Of Swedadhikya (Hyperhidrosis) (International Journal of Environmental Sciences, 2025)
The word Ayurveda means "Science of Life." Ayurvedic information began in India 5,000 years ago and is often referred to as the prior "Mother of All Healing." The word cosmetic is derived from the Greek word “Kosmeticos” meaning having the power to arrange skilled in decorating. The term cosmetics article intended to be rubbed, poured, sprinkled or sprayed on, introduced into, or otherwise applied to the human body for cleansing, beutifying and promoting attractiveness. Sweating is a bodily function that helps regulate your body temperature, that’s function called perspiration and it is the release of a salt-based fluid from your sweat glands. The moist environment created by Hyperhidrosis condition, creates an ideal conditions for an overgrowth of bacteria. In hyperhidrosis, bacteria break down certain proteins in the sweat into acids, so it is not the bacteria that stink. It is the by-product of the bacteria breaking down the protein. However, the odour developing via degradation of sweat by bacteria can be embarrassing, can affect self-esteem, and can have psychological consequences. Therefore, deodorants and antiperspirants are an essential part of most consumers’ daily personal care routine. Objectives: To observe, and Standardize the Pharmaceutical & Analytical and clinical trial parameters of Shirishadi Sharir Daurgandhyahara(SSD) Powder & SSD Spray in Swedadhikya condition. Methods: A cross-sectional observational study was conducted on 30 volunteers divided into 2 groups: Group-A, Group-B with 15 participants in each group.